Effect of Er : YAG and diode lasers on the adhesion of blood components and on the morphology of irradiated root surfaces - Theodoro, Letícia Helena [UNESP]; Sampaio, Jose Eduardo C.; Haypek, Patricia; Bachmann, Luciano; Zezell, Denise Maria; Garcia, Valdir Gouveia (Wiley-Blackwell, 2006)
Objectives: the aim of this study was to evaluate in vitro, by scanning electron microscopy (SEM), the adhesion of blood components on root surfaces irradiated with Er:YAG (2.94 mu m) and GaAlAs Diode (808 nm) lasers and the effects on the morphology of irradiated root surfaces.Methods: One hundred samples of human teeth were obtained. They were previously planed and scaled with manual instruments and divided into five groups of 20 samples each: G1 (control group) - absence of treatment; G2 - Er:YAG laser (7.6 J/cm(2)); G3 - Er:YAG laser (12.9 J/cm(2)); G4 - Diode laser (90 J/cm(2)) and G5 - Diode laser (108 J/cm(2)). After these treatments, 10 samples of each group received a blood tissue but the remaining 10 did not. After laboratory treatments, the samples were obtained by SEM, the photomicrographs were analysed by the score of adhesion of blood components and the results were statistically analysed (Kruskall-Wallis and Mann-Whitney test).Results: In relation to the adhesion of blood components, the study showed no significant differences between the control group and the groups treated with Er:YAG laser (p = 0.9633 and 0.6229). Diode laser radiation was less effective than control group and Er:YAG laser radiation (p < 0.01).Conclusion: None of the proposed treatments increased the adhesion of blood components in a significant way when compared to the control group. Although the Er:YAG laser did not interfere in the adhesion of blood components, it caused more changes on the root surface, whereas the Diode laser inhibited the adhesion.
Keywords: blood; fibrin; lasers; root planing